2013
DOI: 10.6061/clinics/2013(12)02
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-brachial index as a predictor of coronary disease events in elderly patients submitted to coronary angiography

Abstract: OBJECTIVES:To correlate the importance of the ankle-brachial index in terms of cardiovascular morbimortality and the extent of coronary arterial disease amongst elderly patients without clinical manifestations of lower limb peripheral arterial disease.METHODS:We analyzed prospective data from 100 patients over 65 years of age with coronary arterial disease, as confirmed by coronary angiography, and with over 70% stenosis of at least one sub-epicardial coronary artery. We measured the ankle-brachial index immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Studies have shown that patients with an ABI < 0.9 had a higher prevalence of multi-vessel CAD than those with a normal index [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with an ABI < 0.9 had a higher prevalence of multi-vessel CAD than those with a normal index [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, most of the patients belonged to age group of 51 -60 years. It is known that ageing leads to decreased ankle-brachial index as a result of arterial stiffening [13]. Further, a significant male predominance is commonly observed in majority of studies on coronary artery disease and peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, ABI < 0.90 is associated with a worse cardiovascular prognosis and increased all-cause mortality. [11][12][13][14][15] Although ABI is useful for detecting PAD, its validity in predicting CAD is not well established.…”
Section: Resultsmentioning
confidence: 99%